IMPACT OF TWISTED DUCTS WITH DIFFERENT TWIST RATIOS ON HEAT TRANSFER AND FLUID CHARACTERISTICS OF NiO/WATER NANOFLUID FLOW UNDER MAGNETIC FIELD EFFECT - Arslan, Kami̇l; Pazarlıoğlu, Hayati Kadir; Gürdal, Mehmet; Tekir, Mutlu; Gedik, Engin (Begell House, 2022)
Laminar forced convection of NiO/water nanofluid in a twisted square duct has been investigated numerically under the effect of an external magnetic field (B = 0 G, 450 G, and 550 G) in the Reynolds number range of 500 ≤ Re ≤ 2000. Four different twist ratios (D/L = 0.0, 1.0, 1.5, and 2.0) of the square duct have also been examined. The nanoparticle volume fractions (NPVF) of NiO/water nanofluid have been selected between 0.6 vol.% and 2.5 vol.%. The effects of the magnitude of the magnetic field (MF), twist ratio, Reynolds number, and nanoparticle volume fraction on thermohydraulic performance have been examined by using the homogeneous model in the numerical analyses. The results of the numerical computations have been reported with average Nusselt number Nu, pressure loss, average Darcy friction factor f, and performance evaluation criterion (PEC). The highest heat transfer increment by 20% has been achieved at D/L = 2.0 with the highest nanoparticle volume fraction, namely, 2.5 vol.% NiO/water nanofluid, compared to the case of distilled water (DW) flowing in a plain duct (PD). In addition, it was determined that the magnetic field effect increases the convective heat transfer in the twisted duct with D/L = 2.0 up to 35% compared to the cases in the absence of a magnetic field at D/L = 2.0. Among all cases, the highest PEC has been obtained with 2.5 vol.% NiO/water nanofluid flowing in the twisted duct with the twist ratio D/L = 2.0.